Pelatihan dan Pemberdayaan Kader Posyandu dalam Pemanfaatan Makanan Fermentasi Tradisional Kuansing untuk Peningkatan Gizi Ibu Hamil dan Balita - Ismawati, Ismawati; saryono, saryono; mukhyarjon, mukhyarjon; enikarmila Asni; Devi, Silvera; Anggraini, Suci; Suraya, Nabella; Kesya, Lunari; Salsabila, Dinda; Deanra, Cantika Natswa (Jurnal Pengabdian UntukMu NegeRI, 2025)
Stunting in children remains a health problem in Indonesia. One way to improve the nutritional status of the community to prevent stunting is by utilizing nutrient-rich traditional fermented foods. This community service activity aimed to enhance the knowledge and skills of Posyandu cadres in utilizing conventional fermented foods from Kuansing as a nutritional source for pregnant women and toddlers. The training was conducted on August 30, 2025, at the Gunung Toar Sub-district Multipurpose Hall, Kuantan Singingi Regency, attended by 26 Posyandu cadres. The methods included educational video screening, booklet distribution, interactive discussions, and demonstrations of traditional fermented products such as pekasam, sarobuong, and puduong. Evaluation results showed an increase in participants' knowledge scores from an average of 50 to 70 after the training. This activity demonstrates the effectiveness of science-based education in improving community nutrition awareness and preserving local fermented foods.